2008
DOI: 10.1152/ajpgi.90247.2008
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of theLasp-1gene is linked to increases in histamine-stimulated gastric HCl secretion

Abstract: Lasp-1 (LIM and SH3 domain protein 1) is a multidomain actin-binding protein that is differentially expressed within epithelial tissues and brain. In the gastric mucosa, Lasp-1 is highly expressed in the HCl-secreting parietal cell, where it is prominently localized within the F-actin-rich subcellular regions. Histamine-induced elevation of parietal cell [cAMP]i increases Lasp-1 phosphorylation, which is correlated with activation of HCl secretion. To determine whether Lasp-1 is involved in the regulation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…5D, 5E). Lasp1, a protein expressed in gastric glands [37] has been shown to be downregulated by Sox2 in ES cells [38]. Indeed, we found that Lasp1 was barely detectable in control Sox2 loxP/lacZ gastric glands, but it was strongly upregulated in Sox2 loxP/lacZ ; Blimp1 Cre mutants (Supporting Information Fig.…”
Section: Sox2 Is Required For the Development Of Eye And Foregut Endomentioning
confidence: 73%
“…5D, 5E). Lasp1, a protein expressed in gastric glands [37] has been shown to be downregulated by Sox2 in ES cells [38]. Indeed, we found that Lasp1 was barely detectable in control Sox2 loxP/lacZ gastric glands, but it was strongly upregulated in Sox2 loxP/lacZ ; Blimp1 Cre mutants (Supporting Information Fig.…”
Section: Sox2 Is Required For the Development Of Eye And Foregut Endomentioning
confidence: 73%
“…The QTL region on GGA27 contained two genes that regulate decrease in body weight in mice, i.e., LIM and SH3 protein 1 ( LASP1 ) and phosphatidylinositol - 5 - phosphate 4 - kinase, type II, beta ( PIP4K2B ) [48, 49]. …”
Section: Resultsmentioning
confidence: 99%
“…19 The second protein band from the affinity purification comprised dynamin-1 (Q05193) and dynamin-2 (P50570), again well-known LASP-1-binding proteins. 20 Finally, the 170-kDa protein was identified as ZO-2 (Q9UDY2), a tight junction protein with nuclear-cytoplasmic distribution. 21 The results from the mass spectrometric analysis were confirmed by western blot experiments ( Figure 4a).…”
Section: Identification Of Zo-2 As a Novel Lasp-1-binding Partnermentioning
confidence: 99%